Determinación de las anemias morfológicas y ferropénica en niños con discapacidad menores de 12 años en orfanatos de la Ciudad de Loja - Martínez Luzuriaga, Gabriela Mercedes (2023)
Anemia is the decrease in a person's erythrocyte mass or hemoglobin content below normal values, it constitutes one of the most common problems worldwide. For this reason, the objective was the determination of morphological and iron deficiency anemia in children with disabilities under 12 years of age in orphanages in the city of Loja. The present study had a quantitative approach, of a non-experimental type, with a descriptive cross-sectional design. 115 samples were evaluated, finding a prevalence of 9.6% of microcytes in the morphological analysis. A higher prevalence of microcytic anemia was observed in male children with a percentage of 12.7%. Likewise, cases of iron deficiency anemia were found with a total of 6.1%, being more predominant in males with 7.3%. In addition, a grouping of the samples was carried out according to age, observing that both microcytic anemia and iron deficiency anemia were more prevalent in preadolescents. Although, in anisocytosis and peripheral blood smears, there was no relationship. In addition, MCHC was related to the hypochromia found in the FSP, where a slight decrease in the coloration of microcytic erythrocytes was observed. On the other hand, the relationship between the reticulocyte count and microcytic anemia was determined, where there is a relationship between the two variables due to iron deficiency. Similarly, an analysis of the relationship between disability with the presence of microcytes and iron deficiency anemia was carried out, it was observed that there is no relationship between the variables presented because disability is not a factor for suffering from anemia. Finally, the results of feeding were correlated with the presence of microcytes and iron deficiency anemia, where there is no relationship because the children consume a balanced diet